(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the therapeutic efficacy of Chaihu Jia Longgu Muli Decoction and to analyze its mechanisms of action based on modern pharmacology in combination with traditional medicine pattern differentiation in the treatment of non-organic sleep disorders corresponding to the liver qi stagnation transforming into fire pattern (insomnia syndrome in traditional medicine). Subjects and methods: A prospective, randomized, controlled study was conducted on 70 patients diagnosed with non-organic sleep disorders classified as the liver qi stagnation transforming into fire pattern. Patients were randomly allocated into two groups: the treatment group (n = 35), treated with Chaihu Jia Longgu Muli Decoction, and the control group (n = 35), treated with Longdan Xiegan Decoction. The treatment duration was 20 days. Outcome measures included the PSQI, sleep onset latency, total sleep duration, and changes in traditional medicine-related symptoms before and after treatment. Results: After treatment, both groups showed significant improvements in PSQI scores, reduced sleep onset latency, increased total sleep duration, and alleviation of traditional medicine-related symptoms, including hypochondriac pain, headache and dizziness, irritability, facial flushing, red tongue, yellow tongue coating, dark yellow urine, and wiry rapid pulse (p < 0.05). However, the treatment group demonstrated superior therapeutic efficacy, with rates of good, fair, moderate, and poor outcomes of 34.3%, 51.4%, 11.4%, and 0%, respectively, resulting in an overall effectiveness rate of 97.1%. Improvements in traditional medicine-related symptoms were also significantly greater in the treatment group compared with the control group (p < 0.05). Conclusion: Chaihu Jia Longgu Muli Decoction is more effective than Longdan Xiegan Decoction in the treatment of non-organic sleep disorders of the liver qi stagnation transforming into fire pattern. Its therapeutic efficacy is supported by clinical evidence and is consistent with modern pharmacological mechanisms as well as traditional medicine principles of pattern differentiation and formula composition, confirming the scientific basis and clinical applicability of the formula.